1999
DOI: 10.1016/s0375-9601(99)00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric anomalies of solid CO and N2 in the audio frequency range

Abstract: Physics Letters A 256 (1999) 75-80. doi:10.1016/S0375-9601(99)00217-0Received by publisher: 1999-03-19Harvest Date: 2016-01-04 12:22:22DOI: 10.1016/S0375-9601(99)00217-0Page Range: 75-8

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In addition to the above results, the results of previous studies [8][9][10] showed dramatic aging effects as a function of the applied ac electric fields and the thermal history of the sample. Figure 4 shows the dielectric response of a 70% N 2 -Ar sample, first cooled to 4.2 K in zero field, then warmed up to 54 K in 5 kV/m and 1 kHz excitation fields.…”
Section: B Electric Field Dependent Behavior In the Glass Statesupporting
confidence: 68%
See 2 more Smart Citations
“…In addition to the above results, the results of previous studies [8][9][10] showed dramatic aging effects as a function of the applied ac electric fields and the thermal history of the sample. Figure 4 shows the dielectric response of a 70% N 2 -Ar sample, first cooled to 4.2 K in zero field, then warmed up to 54 K in 5 kV/m and 1 kHz excitation fields.…”
Section: B Electric Field Dependent Behavior In the Glass Statesupporting
confidence: 68%
“…The experiments were stimulated by the striking field-cooling effects observed recently in the electric susceptibility measurements of solid N 2 . [8][9][10] When field-cooled from high temperature in the presence of a small ac electric excitation field, pure N 2 showed distinct memory and aging effects even on cooling into the low temperature fcc phase. This electric field induced behavior occurs without the presence of disorder and is believed to result from the complex geometrical nature of the frustration of the interactions and steric hindrance that lead to a significant coupling of the center-ofmass positions of the molecules and the relative orientations of the molecular axes.…”
Section: Fig 1 N 2 -Ar Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…For dielectric fields with ε r = 1.24 and ε r = 1.80, the anharmonic frequencies are 1009 cm −1 and 700 cm −1 , respectively. It is well known that N 2 matrix has a larger effect on the infrared spectra of trapped molecules than Ar or Kr matrices [2], despite the fact that ε r of solid N 2 (1.43 [20]) is smaller than those for solid Ar or Kr. This suggests that the procedure described above for rare gas matrices might not be adequate to account for the effect of an N 2 matrix on the BrH : NH 3 complex.…”
Section: Other Matrices and Correlationsmentioning
confidence: 97%
“…The average polarizability is defined as ␣ 0 = 1 3 ͑␣ ʈ +2␣ Ќ ͒, where ␣ ʈ and ␣ Ќ are the polarizabilities parallel and perpendicular to the molecular axes, respectively. The isotropic component is simply ␣ Ќ and the anisotropic component is given by [23][24][25] …”
Section: Correlations and Memory Effectsmentioning
confidence: 99%